SUSTAINED RELEASE MICROBEADS OF RITONAVIR: IN VITRO AND IN VIVO EVALUATION - VENKATESH, D. NAGASAMY; KUMAR, S. SHASHI; RAJESHKUMAR, RAMAN (International Journal of Applied Pharmaceutics, 2019)
Objective: The main aim of the present investigation was to develop sustained release microbeads of ritonavir that has a shorter half-life (3-5 h) and requires twice a day administration. These formulations exhibit a sustained release of ritonavir that would expect to improve the therapy, better drug utilization, and patient compliance. Methods: Gellan-chitosan and calcium chloride reinforced beads of ritonavir were prepared by ionotropic gelation method employing different concentrations of gellan, chitosan, calcium chloride and drug. The prepared beads were evaluated for various physicochemical parameters such as particle size determination, drug entrapment efficiency, swelling studies, infrared spectroscopy study, differential scanning calorimetry, x-ray diffraction analysis, scanning electron microscopy, in vitro drug release study and in vivo bioavailability studies. Results: From the results, formulation GC-II exhibited higher drug entrapment efficiency (79.65±0.012), higher swelling index, sustained drug release over a period of 24 h, increased oral bioavailability (2.07 times higher than that of pure drug) and decreased elimination rate (2.15 times lesser for ritonavir microbeads) with prolonged elimination half-life (2.15 times more than pure drug) as compared to pure drug. Conclusion: Ritonavir microbeads have demonstrated as a better delivery system for the sustained release of the drug; which may in turn circumvent the drawbacks associated with the conventional therapy.